2016
DOI: 10.1093/neuonc/now063
|View full text |Cite
|
Sign up to set email alerts
|

Restriction spectrum imaging predicts response to bevacizumab in patients with high-grade glioma

Abstract: RSI is less influenced by changes in edema, conferring an advantage of RSI over ADC for evaluating response to anti-angiogenic therapy in patients with HGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…In contrast to mean values that can be diluted by tissue and microenviromental heterogeneity, the lowest 10th percentile value was chosen to represent regions of tumor with the highest cellular density and proliferation. This is consistent with prior reports showing that the lowest representation of ADC using fifth percentile 20 or 10th percentile ADC values 21,22 has a higher correlation with tumor grade and cellular density in comparison with ADC mean values. One limitation of this study was the small sample size, and a larger cohort would be needed to further validate our results.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to mean values that can be diluted by tissue and microenviromental heterogeneity, the lowest 10th percentile value was chosen to represent regions of tumor with the highest cellular density and proliferation. This is consistent with prior reports showing that the lowest representation of ADC using fifth percentile 20 or 10th percentile ADC values 21,22 has a higher correlation with tumor grade and cellular density in comparison with ADC mean values. One limitation of this study was the small sample size, and a larger cohort would be needed to further validate our results.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, RSI’s ability to probe both the scale and geometry of tissue microstructure positions it well to determine whether regional reductions in DTI-derived FA values are due to axonal loss/demyelination versus extracellular changes (e.g., CSF-filled spaces; inflammation) or CFs. We have previously shown the advantage of RSI over standard DTI for reconstructing fiber tracts in regions of peritumoral edema 8 , identifying regions of high cellularity in patients with high grade glioma 16 , and evaluating response to therapy in patients treated with bevacizumab 17 . We now extend the application of RSI to unveiling the complex cytoarchitecture of white matter injury in patients with TLE.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with previous research suggesting that neither FLAIR nor CE volumes are significant predictors of PFS/OS following bevacizumab. 25,31 Rather, quantitative estimates of FLAIR border patterns may have the potential to serve as a reliable biomarker for non-enhancing tumor progression in HGG patients following treatment with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…The patients included in this study represent a subset (33 of 40) of the patients reported in a previous publication that examined the utility of advanced diffusion imaging (i.e., restriction spectrum imaging) for the evaluation of response to bevacizumab. 25 …”
Section: Methodsmentioning
confidence: 99%